Trichodesmium latitudinal distribution on the shelf break in the southwestern Atlantic Ocean during spring and autumn. Issue 11 (28th November 2016) - Detoni, Amália Maria Sacilotto; Ciotti, Áurea Maria; Calil, Paulo H. R.; Tavano, Virginia Maria; Yunes, João Sarkis
Abstract: We report Trichodesmium slicks in the South Atlantic associated with fronts produced by the southward displacement of the Brazil Current. For the first time, a relatively high spatial sampling grid of trichomes density is shown over an undersampled region with regard to Trichodesmium . In this study, the distributions of Trichodesmium along the southeastern Brazilian continental shelf break were characterized during four oceanographic cruises and related to seawater temperature, upper layer nutrient concentrations and wind dynamics. Meridional changes in the densities of trichomes followed an expected trend with higher (lower) values found in warmer (colder) and more saline (less saline) water masses. Between 23° and 28°S, large accumulations of trichomes were associated with high temperature, increased phosphate concentrations (>0.08 μM), nitrogen below 2.4 μM, and low wind speeds (<11 m s −1 ). Maximum densities of 212.6 × 105 trichomes L −1, which are considerably larger than those reported in other studies in subtropical oceans, occurred at stations showing weak water column stability and higher phosphate levels over the upper 25 m. We suggest that shelf break dynamics, which drive and modulate the intensity of the shelf break upwelling, as well as wind divergence at spatial scales of approximately 600 km 2, associated with mesoscale activities, may favor Trichodesmium growth and accumulation. On the other hand, Trichodesmium densities were low at latitudes between 28° and 33°S, likely due to either or both the lowest sea surface temperatures and/or out‐competition by the faster‐growing nondiazotrophs. Key Points: First study about Trichodesmium abundance in the southwestern Atlantic Ocean Environmental factors in the increase of trichome accumulation and in the formation of Trichodesmium slicks Trichodesmium slicks is associated to the dynamic of western boundary current of the South Atlantic